Gestión financiera en la sostenibilidad de los microemprendimientos del sector comercial - Vilema Romero, Diana Carolina (2021)
The pharmaceutical market in Ecuador is one of the sectors that most boost the economy, even though large corporations have a presence in a large part of the market, it is small and medium-sized enterprises that bring stability to the market, whether they offer or acquire goods and services or, generating employment on a large scale. Regardless of the size, every organization requires an efficient financial management that assists in the achievement of its objectives, considering its strengths and limitations in the market in which it operates. However, the reality is that many of these microenterprises see their decline coming much earlier than expected, and the factors that cause it are both internal and external. Internal factors include lack of financial analysis, interference by owners or family members in decision-making, lack of innovation and poor management of human and economic resources. External factors are related to the difficulty in obtaining external financing and high interest rates…………